Identification of infectious microbiota from oral cavity environment of various population group patients as a preventive approach to human health risk factors - Paweł J. Zawadzki (Annals of Agricultural and Environmental Medicine, 2016)
Introduction and objective This study presents the results of comparative investigations aimed to determine microbiota that can occur in the oral environment in different human populations. The objective of the research was to identify pathogenic oral microbiota, the potential cause of health complications in patients of different population groups.